IMPORTANT TASKS IN THE FIELD OF FRUIT GROWING IN KARAKALPAKSTAN - Sarsenbaeva Sapura Jaqsiliq qizi (TADQIQOTLAR.UZ, 2023)
Abstract. The article talks about the climatic conditions of the Republic of Karakalpakstan and its special weather. Changes in climate and the advantages of growing figs under these conditions are studied. It was said about the cultivation of fruits in an ecological environment.